Аналіз практичної стійкості та чутливості лінійних динамічних систем зі зміною вимірності фазового простору - Garashenko, Fedir G.; Soproniyk, Olga L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2016)
In this work, the models of linear parametric systems of ordinary differential equations with variable measurability of phase space are investigated. The theorems about the practical stability of linear parametrical systems with variable measurability are proved. It is important that the reverse theorem about practical stability of indicated systems is obtained. The algorithms and criteria of analysis of practical stability of linear parametrical systems with variable measurability of phase space at the presence of constantly occurring perturbations are shown. The matrix equations of sensitivity of linear parametrical systems with variable measurability of the phase space are researched. It was investigated that on the basis of methods of practical stability and conditions which satisfied sensitivity matrices it was possible to effectively find the estimations of parameters for an analysis of the system sensitivity with variable measurability of the phase space. Results of given investigations can be successfully applied in the tasks of digital data processing and pattern recognition.